2022
DOI: 10.1002/job.2647
|View full text |Cite
|
Sign up to set email alerts
|

All set in stone? How essentialist beliefs about aging affect older workers' motivation to continue working beyond retirement age

Abstract: Although population aging requires that employees increasingly work beyond traditional retirement ages, negative age stereotypes often portray older workers as unwilling or unable to work longer. However, recent lifespan developmental research suggests that there are significant individual differences in how fixed versus malleable people perceive the aging process possibly affecting how they envision their occupational future. We develop and test a theoretical model on the role of essentialist beliefs about ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…Previous studies assessing promotive voice revealed that employees communicating constructive and creative ideas to ensure organisational improvements would be beneficial for corporate development (Maynes & Podsakoff, 2014). Constructive behaviour allows employees to evaluate personal workplace demeanours and encourages 4 supervisors to provide more organisational resources and positive treatments (Cheng et al, 2013;He, Morrison & Zhang, 2021;Weiss, Weiss & Zacher, 2022). Subordinates with higher resource accessibility would possess comprehensive control of job executions, which boosts work performance evaluations.…”
Section: The Mediating Role Of the Lmx Qualitymentioning
confidence: 99%
“…Previous studies assessing promotive voice revealed that employees communicating constructive and creative ideas to ensure organisational improvements would be beneficial for corporate development (Maynes & Podsakoff, 2014). Constructive behaviour allows employees to evaluate personal workplace demeanours and encourages 4 supervisors to provide more organisational resources and positive treatments (Cheng et al, 2013;He, Morrison & Zhang, 2021;Weiss, Weiss & Zacher, 2022). Subordinates with higher resource accessibility would possess comprehensive control of job executions, which boosts work performance evaluations.…”
Section: The Mediating Role Of the Lmx Qualitymentioning
confidence: 99%
“…Second, organizations can promote OFTP by influencing employees' mindset about ageing. Weiss et al (2022) found that individuals who believed that ageing was a fixed rather than a modifiable process had more constrained OFTP. Furthermore, in their experimental study, the results demonstrated that a relatively simple intervention (i.e., manipulating essential beliefs about ageing using a newspaper article) can change such a mindset.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Such theory lends itself to explanations of withdrawal from work. Nevertheless, very few retirement studies have employed this theoretical approach (Fasbender et al, 2019; Griffin et al, 2012; Weiss et al, 2022). In our study, we use this framework to help explain variations in change over time in older workers' retirement intentions, focusing on health and manager support.…”
Section: Introductionmentioning
confidence: 99%